PELAKSANAAN PUTUSAN PENGADILAN TERHADAP TINDAK PIDANA ANAK YANG DIKEMBALIKAN KEPADA ORANG TUA - Nuraini, Septi; Yunaldi, Wendra; Munandar, Syaiful (Ensiklopedia of Journal, 2024)
The rapid development of culture, science, and technology has an impact on children's behavior in social life. The behavior of children in this development is by the norms and some are not by the norms. Behavior that is not in accordance with the norm will cause problems in the field of law and harm the community. So it is necessary to punish children who are regulated separately in the Juvenile Criminal Justice System with more emphasis on improving the child of the perpetrator of a crime with the aim of not merely imposing a crime but also using certain actions (maatzegel) and not punitive but for the improvement of the child. Implementing the court decisions in the form of actions such as returning children in conflict with the law to their parents, has not been carried out properly because there are still obstacles faced by the Prosecutor and Community Advisors in supervising and guiding children who are returned to their parents. This research is juridical empirical research that is descriptive. The data used is the main data, namely interviews with the Attorney and Community Advisors. Based on the results of this research on Court Decision 43/Pid.Sus.Anak/2022/PN.Pdg The child is returned to the parents, after the child is detained in the detention center from 08 October 2022 to 14 November 2022 with several extensions, then it is decided on 03 November 2022. In implementing this decision, there are two obstacles: the child is not immediately returned to the parents after being terminated due to administrative issues and the decision does not state supervision, guidance, and coaching by the Supervisor. So that the child does not receive supervision, guidance, or coaching after being returned to the parents.Keywords: children in conflict with the law; criminal acts of children, the implementation of court decisions